The adherence and tolerance of adjuvant endocrine therapy in geriatric breast cancer patients - Meng-Ting Peng; Shin-Cheh Chen; Wen-Chi Shen; Yung-Chang Lin; Hsien-Kun Chang (Journal of Cancer Research and Practice, 2016)
Background: Adherence to and tolerance of oral adjuvant endocrine therapy (ET) are important to improve survival for hormone receptor (HR)-positive breast cancer patients. To date, there has been limited literature discussing this issue in elderly patients. Herein we have presented a retrospective study to analyze the tolerance to and completion rate of ET in a single medical center in Taiwan. Patients and methods: From 1996 to 2009, a total of 269 female patients over 70 years of age with primary HR-positive operable breast cancer were registered and analyzed for this study. Results: In our study, the completion rate was 49.4% for all 269 patients and was 56.7% for those willing to initiate ET. Of the 72 patients that discontinued ET early but not due to recurrence, 9.7% had well-documented ET-related adverse events, 33.3% refused to undergo ET but remained in follow-up, 44.4% did not undergo ET because of loss of follow-up before a complete ET period, and 12.5% of the patients discontinued ET arising from other medical conditions. The switch therapy, tamoxifen followed by aromatase inhibitor, showed a greater completion rate, compared with upfront tamoxifen or aromatase inhibitor. Conclusions: The completion rate for patients who underwent oral ET in our study was similar to previous studies. The switch method of adjuvant oral endocrine therapy demonstrated a better tolerance and adherence in elderly breast cancer patients, compared with tamoxifen or aromatase inhibitor alone.